Imaging fluid - rich zones by magnetotelluric method at south Marmara region - Cengiz, Özlem. (Thesis (M.S.) - Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2012., 2012)
Magnetotelluric data at sixteen sounding locations along two parallel profiles at south Marmara region were collected to improve the understanding of the crustal electrical conductivity structure. The PW (~40 km) and PE (~35 km) profiles yield data in the frequency range 320-0.0005 Hz. Remote reference technique (Gamble et al., 1979) was used to enhance the data quality. The effects of near surface inhomogenities (galvanic distortions) were removed from the data utilizing Groom and Bailey (1989) decomposition. Following the decomposition, the geoelectric strikes of N102°E and N72°E were calculated for the PW and PE profiles, respectively. The data were rotated using these strike directions. Following this step, they were modeled in two dimensions using the inversion code developed by Ogawa and Uchida (Ogawa and Uchida, 1996), with error floors of 10 per cent for apparent resistivity and 2.86° for phase of both TE (transverse electric) and TM (transverse magnetic) modes. Resulting models suggest that the South Marmara fault possibly corresponds to a lateral resistive boundary between Manyas-Karacabey basin and Bandırma-Karadağ uplift on the PW and Uluabat uplift and Mudanya uplift on the PE profile. The features characterized in geoelectric models also correlate with known faults in the study area. While the conductive zones beneath the northern ends of the profiles at depths greater than 13 km are attributed to partially melting in the crust or the existence of deep crustal fluids below the impermeable layers, the highly resistive zones are associated with low fluid condition and high rigidity.
Keywords: Magnetotelluric prospecting.; Galvanomagnetic effects -- Mathematical models.